Sexual Dimorphism in Drug Metabolism and Pharmacokinetics - Valodara, Askhi M.; SR, Kaid J. (Current Drug Metabolism, 2019)
Background: Sex and gender-based differences are observed well beyond the sex organs and affect several physiological and biochemical processes involved in the metabolism of drug molecules. It is essential to understand not only the sex and gender-based differences in the metabolism of the drug but also the molecular mechanisms involved in the regulation of drug metabolism for avoiding sex-related adverse effects of drugs in the human. Methods: The articles on the sex and gender-based differences in the metabolism of drug molecules were retrieved from the Pub Med database. The articles were classified into the metabolism of the drug molecule, gene expression regulation of drug-metabolizing enzymes, the effect of sex hormones on the metabolism of drug, expression of drugmetabolizing enzymes, etc. Results: Several drug molecules are known, which are metabolized differently in males and females. These differences in metabolism may be due to the genomic and non-genomic action of sex hormones. Several other drug molecules still require further evaluation at the molecular level regarding the sex and gender-based differences in their metabolism. Attention is also required at the effect of signaling cascades associated with the metabolism of drug molecules. Conclusion: Sex and gender-based differences in the metabolism of drugs exist at various levels and it may be due to the genomic and non-genomic action of sex hormones. Detailed understanding of the effect of sex and related condition on the metabolism of drug molecules will help clinicians to determine the effective therapeutic doses of drugs dependingon the condition of patient and disease.
Keywords: pharmacokinetics